Penerapan Pendekatan Saintifik Berbasis Mind Mapping Untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika(PTK Pada Siswa Kelas VII A SMP Muhammadiyah 5 SurakartaTahun Ajaran 2014/2015) - Pratama, Yotam Agung, Dra. Nining Setyaningsih, M.Si (2015)
The goal of this research is to improve students' mathematics problem solving abilities by applying a scientific approach based Mind Mapping. This research is a classroom action research. Subject recipient of action that students of grade VII A of Muhammadiyah 5 Surakarta Junior High School totaling 32 students and giver of action that is the subject of mathematics teachers who collaborate with researchers. A method of data collection is done by observation, documentation, test questions and field record sheet. A technique of data analysis consists of: data reduction, data presentation and conclusion. The results showed an increase in students' mathematical problem solving ability through scientific approaches based Mind Mapping. It can be seen from the increase in the percentage of indicators mathematical problem solving abilities, that is (1) the ability to understand the problems of an increase of (53.125%), before the action (31.25%) increased to (84.375%); (2) the ability of the completion strategy planned an increase of (59.375%), before the action (18.75%) increased to (78.125%); (3) ability to implement strategies to solving issue an increase of (55.75%), before the action (12.5%) increased to (68.25%); and (4) conduct re-examination of the answers given an increase of (59.375%), before the action (0%) increased to (59.375%). From these results it can be concluded that the application of the scientific approach based Mind Mapping can improve students' mathematics problem solving ability in mathematics.